Cluster analysis of the frequency of use of spreadsheet functionalities - Raković, Lazar; Sakal, Marton; Matković, Predrag (Anali Ekonomskog fakulteta u Subotici, 2020)
Presenting a part of the results of a broader research into the use of spreadsheet programs in micro, small and medium sized enterprises on the territory of the Republic of Serbia, the article examines the differ-ences in the manner and purpose of use of spreadsheet programs by respondents of various levels of knowledge and experience through creating clusters of rarely, moderately and frequently used functionalities of these programs. The research results have shown that greater experience, better awareness about the possibili-ties of spreadsheet programs, and being better versed in the use of spreadsheets do not necessary result in a more frequent use of functionalities that can significantly mitigate the risks of their use.